2016
DOI: 10.1017/s0029665116000707
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition in the spotlight: metabolic effects of environmental light

Abstract: Use of artificial light resulted in relative independence from the natural light-dark (LD) cycle, allowing human subjects to shift the timing of food intake and work to convenient times. However, the increase in artificial light exposure parallels the increase in obesity prevalence. Light is the dominant Zeitgeber for the central circadian clock, which resides within the hypothalamic suprachiasmatic nucleus, and coordinates daily rhythm in feeding behaviour and metabolism. Eating during inappropriate light con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 146 publications
(188 reference statements)
0
18
0
1
Order By: Relevance
“…Animal and human studies providing evidence of the metabolic effects of environmental light have been reviewed extensively (Cho et al ; Versteeg et al ). In humans, increases in obesity and diabetes match increased artificial light exposure (Fonken and Nelson ) and it has been demonstrated that evening bright light increases appetite (AlBreiki et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Animal and human studies providing evidence of the metabolic effects of environmental light have been reviewed extensively (Cho et al ; Versteeg et al ). In humans, increases in obesity and diabetes match increased artificial light exposure (Fonken and Nelson ) and it has been demonstrated that evening bright light increases appetite (AlBreiki et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the many potential environmental factors causing obesity, reaching from viruses 72 through toxins 73 to the use of artificial light 74 , changes in nutrition and food hedonics have attracted the most attention. Particularly the shift away from relatively low-calorie, high-fiber diets towards energy-dense, palatable diets is considered an important contributor to the increased prevalence of obesity.…”
Section: Neural Regulation Of Body Weightmentioning
confidence: 99%
“…An important background perspective to this scenario is the escalating global epidemics of type 2 diabetes mellitus (T2DM) and cardiovascular disease (CVD) against the dramatic changes that have occurred in Western and even traditional‐living societies over recent decades with globalization and modernization . This includes changes in light exposure resulting from the extensive use of artificial light (‘light pollution’) , controlled ambient temperature and constant food availability , societal and workplace stresses, increasing shift work in the workplace and industry, jet travel with time zone changes and changes in nutrition. In the light of this, it has been suggested that the resulting circadian rhythm disturbances may be a major contributor to the contemporary global epidemics of T2DM, CVD and obesity .…”
Section: Introductionmentioning
confidence: 99%
“…It regulates gene expression, release of various hormones, body temperature, activity pattern, energy expenditure and other important body functions. This being the case, it is not surprising that there has been significant interest in the relationship of circadian disruption with glucose metabolism [5,13,15,16,18,21,22] and other components of the Metabolic Syndrome [6,17,19,22,23].…”
Section: Introductionmentioning
confidence: 99%